Collic evoked potentials, myogenic potentials (CEMPs) and postural responses produced by brief 100 Hz vibration of the sternocleidomastoid muscle. (11th June 2022) - Todd, Neil P.M.; Govender, Sendhil; Colebatch, James G.
Highlights: We report novel collic evoked responses from 100 Hz impulses applied to the sternocleidomastoid muscle. Evoked responses were observed in ipsilateral extraocular and cerebellar electrodes. The extraocular response may underlie compensation for vestibular lesions. The postural response appears to be a spino-bulbar-spinal reflex. Cortical potentials occured at FCz and postural responses in leg muscles. Abstract: We present an initial report using 5 subjects, of short and long latency collic evoked responses following a half cycle of 100 Hz vibration (5 ms) applied to the sternocleidomastoid (SCM) tendon. These were detected in EEG and extraocular and leg muscles and compared with vestibular-dependent responses from direct mastoid stimulation. The responses from the extraocular recording site are likely to be evoked myogenic potentials, thus "collic evoked myogenic potentials" (CEMPs). An n19/p24 presumed ocular CEMP (oCEMP) was followed by a P22/N28 response over the posterior fossa, referred to as a collic cerebellar evoked potential (CoCEP), with responses in leg muscles starting around 55 ms. In contrast to their vestibular analogues, the oCEMP and CoCEP were predominantly ipsilateral to the side of stimulation, consistent with a double-crossed projection. In addition, their thresholds were just above the threshold of vibrotactile sensation, implying a low threshold, oligo-synaptic projection of SCM afferents to both extraocular and cerebellar targets. Following these short latency responses, SCM tendon stimulation evoked prolonged EMG responses in postural muscles of the legs, consistent with a role in the afferent limb of a short latency, spino-bulbar-spinal postural response to sternal perturbations. These collic evoked responses are likely to be of value in understanding the functions of cervical muscle afferents and have clinical value, for example in monitoring compensation after vestibular loss.